2001
DOI: 10.1038/sj.onc.1204868
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the RelB gene is regulated by NF-κB

Abstract: RelA and RelB are two members of the NF-kB family that dier structurally and functionally. While RelA is regulated through its cytosolic localization by inhibitor proteins or IkB and not through transcriptional mechanisms, the regulation of RelB is poorly understood. In this study we demonstrate that stimuli (TNF or LPS) lead within minutes to the nuclear translocation of RelA, but require hours to result in the nuclear translocation of RelB. The delayed nuclear translocation of RelB correlates with increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
154
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 43 publications
25
154
1
2
Order By: Relevance
“…TNF treatment for 3 h also resulted in an increase in p100 and RelB levels. This was in agreement with previous studies that described the degradation and resynthesis of IB␣ and the induction of p100 and RelB by the classical NF-B signaling pathway following TNF treatment (19). In contrast, a reduction of p100 was observed 3 h after the treatment with agonistic LT␤R mAb (compare lanes 1 and 6 -9) with a corresponding increase in nuclear p52 (Fig.…”
Section: Resultssupporting
confidence: 93%
“…TNF treatment for 3 h also resulted in an increase in p100 and RelB levels. This was in agreement with previous studies that described the degradation and resynthesis of IB␣ and the induction of p100 and RelB by the classical NF-B signaling pathway following TNF treatment (19). In contrast, a reduction of p100 was observed 3 h after the treatment with agonistic LT␤R mAb (compare lanes 1 and 6 -9) with a corresponding increase in nuclear p52 (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Early studies showed that the promoter regions of relb and nfκb2 genes contain κB-binding sites and transcriptional regulation of these two genes is dependent on RelA [105,106]. LTβR signaling was shown to activate RelA:p50 followed by RelB:p52 via two distinct pathways [107].…”
Section: Rela:p50 Control Of Non-canonical Signalingmentioning
confidence: 99%
“…Thus, RelB binding to the MnSOD promoter may allow for more accessibility for binding of other transcription factors including Sp1 (Xu et al, 2002) and coactivators (nucleophosmin) (Dhar et al, 2004). RelB itself could activate its own gene (Bren et al, 2001) and additional transcription factors to activate the MnSOD gene in response to radiation. Consistent with the induction of MnSOD, a time-dependent increase in MnSOD protein was observed paralleling the MnSOD mRNA levels Figure 1 Increased nuclear protein levels of RelB correlate with intrinsic radiation resistance.…”
Section: Relb Enhances Radiation Resistance S Josson Et Almentioning
confidence: 99%